Hubungan Pengetahuan dengan Kejadian Sectio Caesarea Pada Ibu Bersalin di Bangsal Kebidanan RSU Maijand H.A Thalib - Emitra Fatriona (Malahayati Nursing Journal, 2022)
ABSTRACT: CORRELATION OF MOM’S KNOWLEDGE AND THE CASE OF CAESARIAN BIRTH IN OBSTETRIC WARD OF RSU MAIJAND H.A DISTRICT HOSPITAL IN SUNGAI PENUH IN 2021. Caesarian birth is designated for special medical indication, either from the mom or from the fetus. Caesarian birth should be considered as an alternative only when the normal birth can’t be followed due to some medical indication. Although 90% of birth process are classified as normal birth without complication, but when the complication happened the medical treatment taken should prioritize the health of mom and fetus. Caesarian birth should be treated as the last option of giving birth when normal birth can’t be done due to some medical indication. This research is being conducted with the purpose of exploring the correlation of mom’s knowledge and the case of caesarian birth in obstetric ward of RSU Mayjend H.a talib district hospital Kerinci in 2021.This research is an analytical descriptive with cross-sectional study in obstetic ward of RSU. mayjend District Hospital in Sungai Penuh with 30 respondents, using questionnaire and medical record in the obstetric ward, and it found that 24 of them (80%) are having caesarian birth, while 6 respondents (20%) are having normal birth. It starts with editing, coding, data entry, tabulating and cleaning, then being analyzed with uni-variat and bi-variat using chi-square test. Coming from the result of this research, we found that 80% of the data are having caesarian birth, and 63.3% of them are driven by lack of knowledge of the mom. the moms are having a record/history with caesarian in the previous birth, 6,7% are There is a relationship between knowledge and sectio caesarea of Rsu. Mayjend h.A thalib district hospital in Sungai Penuh in 2021. Statistic test result using chi-square shows that p=0,0032(p0.05). Therefore, it’s being suggested to medical staff and nurses to provide an education to moms regarding normal birth and its pathologies during ANC, in order to be mom’s consideration on choosing the correct way of giving birth. Keywords: Case of caesarian, knowledge     INTISARI: HUBUNGAN PENGETAHUAN  DENGAN KEJADIAN SECTIO CAESAREA PADA IBU BERSALIN DI BANGSAL KEBIDANAN RSU MAYJEND H.A THALIB SUNGAI PENUH TAHUN 2021 Persalinan dengan Sectio Caesarea ditujukan untuk indikasi medis tertentu, baik dari faktor ibu maupun faktor janin. Seharusnya Sectio Caesarea dipahami sebagai alternatif persalinan ketika persalinan normal tidak bisa dilakukan. Meski 90% persalinan dikategorikan persalinan normal tanpa komplikasi, namun apabila terjadi komplikasi maka penanganan selalu berpegang teguh ada kesehatan ibu dan janin. Tindakan Sectio Caesarea  merupakan pilihan persalinan terakhir setelah persalinan pervaginam tidak layak dilakukan. Tujuan Penelitian untuk mengetahui Hubungan pengetahuan dengan kejadian sectio caesrea pada ibu bersalin di bangsal kebidanan RSU Mayjend H.A Thalib Sungai Penuh Tahun 2021.Penelitian ini merupakan penelitian deskriftif analitik dengan cross sectional study yang dilakukan di bangsal Kebidanan RSU. Mayjend H.A Thalib sebanyak 30 responden, yang bersalin dengan  sebanyak 24 (80,0%)  responden dan 6 (20,0%) responden bersalin dengan normal, pada saat penelitian dengan menngunakan kuisioner ddan rekam medik bangsal kebidanan. Di mulai dengan editing, coding, entry,  tabulating, dan cleaning kemudian di analisa secara univariat dan bivariat dengan uji chis- square. Berdasarkan hasil penelitian (80,0%) bersalin dengan Sectio Caesarea,lebih dari separoh (63,3%) pengetahuan kurang baik. Terdapat hubungan antara pengetahuan dengan sectio caesarea di RSU Mayjend H.A Thalib Sungai Penuh tahun 2021, hasil uji statistic menggunakan chi- square di dapatkan nilai p=0,032 (p0,05). Oleh sebab itu di sarankan pada petugas medis dan perawat untuk memberikan penyuluhan kesehatan tentang pengetahuan persalinan normal dan patologis pada saat ANC, sehingga bisa menjadi pertimbangan pada saat melakukan persalinan dengan cara yang tepat. Kata Kunci : Kejadian Sectio caesarea dan Pengetahuan